Folic acid: The key to a healthy pregnancy – A prospective study on fetomaternal outcome - Madhusudan Dey; Pranjali Dhume; Sanjay K Sharma; Suyash Goel; Sunil Chawla; Ankur Shah; G Madhumidh; Reshu Rawala (Tzu Chi Medical Journal)
Objectives: The objective of the study is to study the fetomaternal outcome associated with folic acid deficiency in pregnancy. Materials and Methods: This hospital-based observational study was conducted in the Department of Obstetrics and Gynaecology at Base Hospital, Delhi Cantt, and a total of 351 participants were enrolled who were fulfilling the inclusion criteria. The plasma folic acid level of the selected patients was measured in the booking visit by automated chemiluminescence assay. The cutoff levels of folic acid were taken at 8.6 ng/mL. Based on these values, the study population was divided into two groups, one with folic acid values <8.6 ng/mL and the other with values ≥8.6 ng/mL. Plasma Vitamin B12 levels were measured to check for any concurrent deficiencies. Obstetric outcomes included first- and second-trimester miscarriages, development of anemia, gestational hypertension/preeclampsia, gestational diabetes mellitus, hypothyroidism, placental abruption, and intrauterine fetal growth restriction (FGR). Furthermore, the period of gestation at delivery, fetal weights, APGAR scores at 5 min were documented. The study also considered fetal neural tube defects, intrauterine fetal demise for data collection. Collected data were analyzed statistically to find the association of the above-mentioned outcomes with levels of folic acid. Results: The rate of preterm deliveries was significantly higher in the folic acid group with levels <8.6 ng/mL (16.94%). The incidence of small for gestational age/FGR was higher in the folic acid group with levels <8.6 ng/mL (27.11%) compared to the high folic acid group with levels ≥8.6 ng/mL (13.38%). The differences in the incidence of anemia, gestational hypertension, gestational diabetes, and preeclampsia between the two groups were not statistically significant and no cases of intrauterine fetal demise or placental abruption were observed in either group. Moreover, there was no significant difference in the relative risk of low Apgar scores at 5 min between the two groups. Conclusion: The present study suggests that low folic acid levels during pregnancy are associated with a higher risk of adverse pregnancy outcomes such as anemia, miscarriages, preterm delivery, and FGR. Therefore, adherence to nutritional recommendation of folic acid supplementation during pregnancy is essential to prevent these adverse outcomes.